THE MEANING OF ONE DIRECTION’S SONG’S IN “MIDNIGHT MEMORIES ALBUM” - Amalia, Qhusnul; Abdullah, Abdullah; Nasta, Mardiyanah (Journal of English Literature and Linguistic Studies, 2024)
This research discusses Meaning in the song of One Direction  in the “Midnight Memories” album. It aims to analyze the meaning of the song based on the theory of Leech (1981) and Yule (1960) to analyze the types also to know how the implied meanings are presented in each song. This study used a qualitative descriptive research methodology. The results of this research show that there are 52 extracts describing the types of meaning found of the One Direction songs in "Midnight Memories' ' album. There were 7 types of meaning's found based on the theory of Leech. They were Conceptual (2), connotative (10), affective (8), social (4), Reflected (2), Collocative (1), and thematic (3). There were 6 types of presupposition found also based on Yule (1960) theory, there were existential (5), factive (7), lexical (6), non-factive (4), structural (2) and counterfactual (3). It means that each song contains meanings that the singers want to convey. Based on 52 data observed, the research concluded that the true meaning can be found using the theory of Leech (1981) and the implied meaning also concerned based on Yule's (1960) theory of presuppositions